Clergy, Retirement, and Wholeness: Looking Forward to the Third Age - Halaas, Gwen Wagstrom (Rowman & Littlefield Publishers, 2005)
What would you wish for in retirement? Good health? Financial Stability? A supportive social community? Retiring well is everyone’s goal, but accomplishing this end requires planning and effort. Family physician Gwen Halaas recognizes the challenges professional caregivers such as clergy experience as they try to practice good self-care, particularly as they approach the significant changes inherent in retirement.